Dynamics of populations with two sexes - Pérez, M. Cecilia; Saavedra, E. Adriana; Ferrari, Mariano Andrés (International Journal of Biomathematics)
A mathematical model is presented in order to describe the dynamics of polygamous populations, bearing in mind single individuals of both sexes and the development of reproductive groups. In this context, the description leads us to consider positive homogeneous dynamical systems, establishing conditions for the stationary state existence and its local stability. A fourth pre-reproductive stage was considered, i.e. males and females spend part of their lives before being in condition to reproduce, as a first step to consider more general models. Finally, we parametrized the proposed model using southern elephant seal data, to analyze the direct applicability to a real population. Fil: Pérez, M. Cecilia. Universidad Nacional de la Patagonia "san Juan Bosco". Facultad de Ingeniería - Sede Esquel; Argentina Fil: Saavedra, E. Adriana. Universidad Nacional de la Patagonia; Argentina Fil: Ferrari, Mariano Andrés. Universidad Nacional de la Patagonia. Facultad de Ingeniería. Sede Puerto Madryn; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Nacional Patagónico; Argentina